Dual Energy Computed Tomography Angiography in the Peripheral Arterial Imaging: A Systematic Review of Image Quality, Radiation Dose and Diagnostic Value - Almutairi, Abdulrahman; Sun, Zhonghua (Current Medical Imaging, 2017)
To perform a systematic review of the diagnostic value of dual energy computed tomography angiography (DECTA) in peripheral arterial disease (PAD). PubMed, ProQuest, Medline and ScienceDirect were searched for studies evaluating DECTA compared to conventional computed tomography angiography (CTA) and digital subtraction angiography (DSA) in patients with PAD. Diagnostic value, image quality and radiation dose were analysed and compared. Nine studies comprising a total of 286 patients were found to meet selection criteria where DECTA was used to evaluate lower extremities. The mean estimates of sensitivity and specificity of DECTA were 95.8% (95% CI: 84 to 97.2%) and 79.8% (95% CI: 78 to 97%). Reduction of the contrast medium volume up to 50% was found to achieve an adequate image quality at the optimal keV setting. The mean effective dose for DECTA was 9.51 mSv (95% CI: 7.56 to 11.18 mSv). DECTA is a non-invasive and an accurate diagnostic procedure in the diagnostic assessment of peripheral arterial disease with high diagnostic value.
Keywords: Peripheral arterial disease